Government actions to address the COVID-19 infodemic in states and capitals in the southeastern region of Brazil (Advances in Knowledge Representation, 2025)
The COVID-19 pandemic has required multiple and coordinated actions by the health sectors of states and municipalities to deal with both the disease and the vast amount of misinformation and disinformation that accompanied it.  The general aim of this study was to investigate the actions implemented by the health departments of the states of Espírito Santo, Rio de Janeiro and São Paulo, as well as in their respective capitals, to combat the COVID-19 infodemic. The research, exploratory in nature and qualitative in approach, used a combination of bibliographic and documentary research, consulting the collections available on the websites of the state and municipal health departments, as well as information obtained through the Access Information Law. Content analysis was used to categorize the initiatives observed. A variety of actions were identified, including the production of information materials to combat disinformation, social media monitoring, the creation of observatories and fact-checking actions, as well as making indicators and scientific information available on websites, social networks, booklets and videos, among other strategies.